Women's experiences of making healthcare decisions about their breast cancer: A phenomenological study. (27th January 2016) - Xiong, Mo; Stone, Teresa E.; Turale, Sue; Petrini, Marcia A.
Abstract: There are few studies about how healthcare decisions are made for women with breast cancer in China and this knowledge is vital, both to further develop person‐centered health care and to ensure that women have a voice in their healthcare decisions. This phenomenological study explored the meaning of women's lived experiences of making healthcare decisions about their breast cancer in China. Semistructured, in‐depth interviews were conducted with a purposive sample of eight women with breast cancer. Data were analyzed using Colaizzi's phenomenological analytic method. The results of this study identified four themes: authority and expertise, lack of knowledge, family support, and Chinese cultural and social influences. Women were deferential to medical authority and perceived expertise, but they wanted to be involved to a greater degree in healthcare decisions. It is important for health professionals to optimize women's participation in decision‐making by removing barriers and advocating on their behalf.